Comparison of nutritional and functional properties of BK2 foxtail millet with rice, wheat and maize flour - Meherunnahar, M; Chowdhury, RS; Hoque, MM; Satter, MA; Islam, MF (Progressive Agriculture, 2018)
The proximate composition, mineral contents and functional properties of BK2 FTM flour was determined and compared with three major cereals commonly consumed in Bangladesh like rice, wheat and maize flour. The samples were cleaned of foreign materials, milled and sieved through 60 μm meshes. The results showed that the BK2 FTM flour contained significantly higher (P<0.05) amount of energy (382.01 kcal) and fat (5.01 g/100g) compared to other major cereals. It also took the second highest value of protein, 9.06%, whereas wheat contained 10.39%, Rice, 6.31% and maize, 6.86%. Similarly, BK2 FTM flour enriched with iron 7.01 mg/100g, copper 1.43 mg/100g and phosphorous 595.12 mg/100g. The foaming capacity and bulk density of BK2 FTM flour were very similar to wheat flour. However, it varied significantly (p<0.05) as compared to rice and maize flour. Progressive Agriculture 29 (2): 186-194, 2018